Pengaruh Persepsi Harga, Lokasi dan Fasilitas Terhadap Keputusan Pembelian Pada Perumahan Unram Residence PT. Varindo Lombok Inti - Deny zulfan Husaini; Rusminah HS (Postgraduate, University of Mataram, 2025)
The purpose of this study is to determine the effect of price perception, location, and facilities on consumers' decisions to purchase houses at Unram Residence. This study is based on fierce competition in the property market and high demand for housing in Mataram City, especially around Mataram University. This study employs a quantitative and associative approach. After collecting data through a questionnaire administered to 60 individuals who purchased homes at Unram Residence, multiple linear regression was conducted using Microsoft Office Excel and Statistical Product and Service Solution (SPSS) software. The results indicate that price perception, location, and facilities partially influence consumers' purchasing decisions at Unram Residence. Recommendations for PT. Varindo Lombok Inti include optimizing pricing, location, and facility strategies through dynamic and sustainable approaches. Future researchers are advised to expand the study by exploring psychological factors, brand perception, and the influence of social media for a more comprehensive understanding of purchasing decisions.